Surface production operations. Volume 1, Design of oil-handling systems and facilities - Arnold, Ken, 1942-; Stewart, Maurice (Houston, Tex. : Gulf Pub. Co., 1998)
In this new edition, experts Arnold and Stewart share their many years of in-the-field and class-room experience. Each chapter has been updated with the latest industry information. You will find new sections on: * Oil-and-water separation * Offshore-platform considerations * Factors affecting oil-and-gas separation * Potential operating problems * Scrubbers * Re-entrainment * Drain systems * Hydrocyclones * Multiphase pumps * Reciprocating pump operations * Water droplet size New figures, photos, charts, and tables consolidate hours of details into at-a-glance illustrations. Example problems accompany the update text. With this volumes clear presentation, you will understand the basic concepts and techniques needed to DESIGN, SPECIFY, and OPERATE oilfield surface production facilities. This manual carefully describes the equipment and processes commonly used in oil-water separating and treating systems. It also shows you how to select the appropriate piping and pumping systems. The authors insights and practical suggestions help you understand the art and science of handling produced liquids. With this reference in hand, you can organize the project with a better grasp of the complex parameters needed to design and operate an efficient production facility.
The production facility -- Choosing a process -- Fluid properties -- Two-phase oil and gas separation -- Oil and water separation -- Crude oil treating systems -- Produced-water treating systems -- Pressure drop in piping -- Choosing a line size and wall thickness -- Pumps -- Centrifugal pumps -- Reciprocating pumps -- Organizing the project.
Includes bibliographical references and indexes.
Keywords: Petroleum engineering -- Equipment and supplies; Oil fields -- Equipment and supplies; Oil fields -- Production methods; Electronic books